Penerapan Metode Hayami dalam Analisis Nilai Tambah Pengolahan Ikan Bandeng Menjadi Amplang - Hasiani, Yarna; Maulana Ash'ari, Fuzi; Suslinawati; Pandi (Rawa Sains: Jurnal Sains STIPER Amuntai, 2024)
Fish is a perishable food so special handling is required to maintain its quality. Post-harvest handling of agricultural and fishery products is an activity downstream agribusiness subsystem. Post-harvest handling has an impact on selling prices. This Research aims to analyze the added value of the processing of milkfish (Chanos chanos) into “Amplang” (Indonesian traditional snack) in Rampa Manunggul Village, Sampanahan Subdistrict, Kotabaru Regency, South Kalimantan Province. Data analysis in this research used the Hayami method. Data was collected using the case study method on Amplang processing business "Sinar Laut". The results of this research show that based on the Hayami method analysis. The added value of milkfish processing in the "Sinar Laut" amplang business is IDR. 101,226/ kg of raw materials with a business owner's profit of 65.02% and a value added ratio of 72.30%, the value added ratio is included in the high category, because the value ratio is more than 40%.